Analysis of the Pedagogical Competence of Prospective Primary School Teachers in Terms of Developing Learning Process Assessment Plans - Muhammad Syazali; Nova Fitriani Wahdah (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
The development of pedagogical competence among prospective primary school teachers faces various challenges stemming from the educational environment and the complexity of teaching. To respond to these challenges, studies that examine pedagogical competence from multiple perspectives are needed. However, research from the evaluation aspect is still very limited. This study aimed to analyze the pedagogical competence of prospective primary school teachers in preparing learning process assessment plans. The sample consisted of 62 second-year students. The data collection instrument was student work documents, which were evaluated using an assessment rubric. The scores obtained from this process were converted into quantitative values ranging from 0 to 100. These quantitative values were then analyzed descriptively to obtain the mean, standard deviation, percentiles, and proportion. The analysis showed that the students' pedagogical competence had a mean score of 80.82 ± 5.75. When converted, this quantitative score is equivalent to a B+ grade, which is interpreted as Good. Individually, the lowest score was 65.50, which is comparable to a C grade and is interpreted as Fair. The highest score was 88.50, equivalent to an A grade with an Excellent interpretation. The 25th percentile was 77, comparable to a B grade and interpreted as Good. In terms of proportion, A grades (Excellent) predominated. However, when viewed from the interpretation categories, the highest proportion was the Good interpretation (49.99%). Based on these findings, it can be concluded that student teachers are ready to assess learning outcomes in the classroom. Nonetheless, further improvement is needed to reach the Excellent category.